2021
DOI: 10.1063/5.0063458
|View full text |Cite
|
Sign up to set email alerts
|

The optimized interface characteristics of β -Ga2O3 Schottky barrier diode with low temperature annealing

Abstract: A low temperature controlled annealing technique was utilized to improve the performance of vertical β-gallium oxide (β-Ga2O3) Schottky barrier diodes (SBDs) in this work. The nickel is diffused into Ga2O3, and NiO was formed at the interface between the anode and semiconductor generating p–n junction after low temperature annealing. Simultaneously, the trap state density of interface Ni/Ga2O3 as well as the carbon bonded with oxygen on the surface was reduced, which was proved by the capacitance and conductan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…It is interesting that they found the Schottky barrier height of the device was changed with the variation of temperature, as shown in figure 6(c). This phenomenon is not surprising considering that Ni can be oxidized at a low temperature, thus affecting the homogeneity of the Ni/Ga 2 O 3 interface and altering the Schottky barrier height [59].…”
Section: I-v Measurementmentioning
confidence: 93%
See 1 more Smart Citation
“…It is interesting that they found the Schottky barrier height of the device was changed with the variation of temperature, as shown in figure 6(c). This phenomenon is not surprising considering that Ni can be oxidized at a low temperature, thus affecting the homogeneity of the Ni/Ga 2 O 3 interface and altering the Schottky barrier height [59].…”
Section: I-v Measurementmentioning
confidence: 93%
“…It is surprising that, although the contact of the four metals with Ga 2 O 3 should have shown Schottky characteristics, all four materials showed Ohmic contacts with Ga 2 O 3 after annealing, which can be attributed to the atom diffusion at the metal/Ga 2 O 3 interface. Hong et al [59] fabricated a Ni-Ga 2 O 3 contact and improved the quality through low temperature post-annealing. After post-annealing, they found that the I off of the device could decrease by two to three magnitudes, which can be attributed to the quality improvement of the Ni-Ga 2 O 3 contact and can be explained by the formation of NiO after annealing.…”
Section: Post-annealingmentioning
confidence: 99%
“…A controlled post low temperature annealing from 100 to 200 °C was observed to improve the performance of vertical Ni/β-Ga 2 O 3 SBDs on the HVPE-grown (001) β-Ga 2 O 3 epilayer . Through postannealing at 200 °C, leakage current decreased by three magnitudes from 1.21 × 10 –6 to 5.12 × 10 –9 A/cm 2 , and SBH increased from 1.07 to 1.14 eV.…”
Section: Schottky Contacts To Ga2o3mentioning
confidence: 98%
“…However, R on and V on were increased from 4.81 mΩ·cm 2 and 0.70 eV to 8.96 mΩ·cm 2 and 0.80 eV, respectively. The improved device performance was attributed to the enhanced interface quality due to compensating the defects at the interface via Ni diffusion in Ga 2 O 3 and the formation of p-type NiO …”
Section: Schottky Contacts To Ga2o3mentioning
confidence: 99%
See 1 more Smart Citation